PEMBAGIAN URUSAN PEMERINTAHAN DI BIDANG KEHUTANAN (antara Pemerintah Pusat, Pemerintah Daerah Provinsi, dan Pemerintah Daerah Kabupaten/Kota) - Yohanes Kambey, Steven (Katalogis, 2015)
This research aimed at exploring (onderzoek) the effectiveness of externalities principle in distributing government authority particularly on the forestry in the relation to running the authority at provincial/city levels and investigating (beoefening) the effectiveness of the distribution and the implementation of responsibility between the government (Ministry of Forestry) and the provincial/city government. This research used a juridical-normative method beginning from the research on juridical doctrine by conducting an inventory of regulations directing the distribution of the government authority on forestry. This continued with the effect of distributing the authority (juridical-sosiological) in order to prescribe legal bases on the forestry authority in the future. It is concluded that the relationship of the externalities among the central, provincial, and regency/city government within the forestry authority based on the criteria of area, the function of forest zone, and the kinds of forest production; and the deconsentration and medebewin tend to be centralised. This brings about inefficiency og public service and low participation of the society in managing forest area and making use of forest sources for improfing the prosperity of the society contributed from foret sector.